A multistatic HF beacon network for ionospheric specification in the Peruvian sector - Hysell, D. L. (2016)
A small network of HF beacon transmitters and receivers has been deployed in Peru for specifying the F region ionosphere in the sector. The effort is motivated by ionospheric disturbances associated with equatorial spread F (ESF) and specifically disturbances arising under inauspicious conditions for ESF as determined by numerical simulations. The beacons operate at dual frequencies (2.72 and 3.64 MHz). They are CW but incorporate pseudorandom noise (PRN) coding so that the group delays of the links can be measured. Other observables are power, Doppler shift, bearing, and polarization. A transmitter is currently deployed at Ancon (11∘46’37’’S, 77∘09’1’’W, 51 m above sea level (asl)), while receivers are at Jicamarca (11∘57’5.8’’S, 76∘52’27’’W, 510 m asl) and Huancayo (12∘02’30’’S, 75∘19’15’’W, 3315 m asl). An algorithm for inverting the beacon data combined with electron density profiles from Jicamarca is described. Data and representative solutions from an experimental campaign held in August 2015 are presented and evaluated.